Effects of Stocking Density and Litter Type on Litter Quality and Growth Performance of Native Chicken - Rohmadi, Dwi; Harimurti, Sri; Wihandoyo, Wihandoyo (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Stocking density gives a significant role in poultry farming, with increasing the number of birds per unit space potentially leading to higher profits. The wider the pen will increase the need litter for pen, rice hulls are commonly used as litter. Limited supplies, higher costs, and unavailability of suitable materials have encouraged the search for alternative litter materials. This study aimed to identify ideal stocking density and other litter material sources on native chickens. The material of this study was 324-day old chick (DOC) native chickens, reared for 10 weeks. The DOC was randomly divided into 9 treatment groups including a combination of 3 stocking densities (8, 12, and 16 chick/m2) and 3 litter materials (rice hulls, wood shavings, and corncobs) in 3 replication. A completely randomized factorial design was applied in the study then followed by Duncan's multiple range tests. The variables observed in this study were litter temperature, litter pH, water holding capacity, ammonia level, final weight, feed consumption, body weight gain, and feed conversion ratio. The results showed that stocking density had only a significant effect (p